Multiplex PCR for Rapid Detection of Rifampin and Isoniazid Resistance in Mycobacterium tuberculosis Isolated from Bandung, Indonesia - IWAN SASKIAWAN; NUR HASANAH (Microbiology Indonesia, 2007)
Mycobacterium tuberculosis resistant to rifampin and isoniazid, known as multidrug-resistant M. tuberculosis (MDR-TB) strains, is an emerging problem of great importance to public health, with higher mortality rates than for drug-sensitive strains. Rifampin resistance is due to mutations on the hot spot region of the rpoB gene, especially at positions 526 and 531, and isoniazid resistance is due to mutation on katG at position 315. Mechanisms of resistance are an appropriate target for molecular genotyping diagnostic methods. Here we examined the multiplex PCR assays for the rapid detection targeting rpoB526, rpoB531, and katG mutations. Sixty-one M. tuberculosis strains were studied based on rpoB526, rpoB531, and katG315 assays employing multiplex PCR. Of the 61 strains, the susceptibility tests determined 42 isolates were MDR-TB strains, 10, 4, and 5 isolates were resistant to rifampin, isoniazid, and at least to six drugs which prescibed for TB, respectively. The mutation profiles of the 42 MDR strains assayed by multiplex PCR were 81 and 38.1% on rpoB and katG, respectively. Six rifampin-resistant isolates (60%) had a mutation on rpoB, 25% isoniazid-resistant isolates had mutation on katG, and 20% of the isolates that were sensitive to all drugs tested had a mutation on rpoB. Sequencing analysis revealed sensitivity of the multiplex PCR assay for rpoB was 98.4% and was 100% for katG. There was a 19% difference between phenotype and genotype properties of all isolates detected. In conclusion, the sensitivity of multiplex PCR method was sufficient for preliminary detection of rpoB and katG mutations, but resistance M. tuberculosis to rifampin and isoniazid were not always conferred by mutated alleles on rpoB and, especially, on katG.